Effect of methionine selenium on growth performance, carcass composition and Se retaining percentage in Lingnan yellow broilers - YIN Zhao-zheng; QIAN Li-chun; LI Xiao-liang (浙江大学学报. 农业与生命科学版)
In this experiment, 600 Lingnan yellow broilers were selected to study the effect of different dosage methionine selenium (Met-Se) on growth performance, selenium retaining percentage and carcass composition. The results were as follows: in test 1, 2, 3 and 4, where the basic diet was supplemented with respectively, 0.1, 0.15, 0.2 and 0.25 mg/kg Se in the form of Met-Se. Correspondingly, bird weight gains were increased by 9.52%(P<0.05), 11.78%(P<0.05), 8.85%(P<0.05) and 8.22%(P<0.05) while feed gain ratio were decreased by 7.25%(P<0.05), 9.78%(P<0.05), 8.70%(P <0.05) and 7.97%(P<0.05), Se retaining percentage were improved by 26.47%(P<0.05), 22.95%(P<0.05), 16.95%(P<0.05) and 16.77%(P<0.05) respectively compared with the control group which was fed with basic diet and 0.15 mg/kg Se in the form of Na2SeO3. The results also indicated that Met-Se did not affect the carcass composition of the broilers.